Effect of periodontal treatment on glycemic control of patients with diabetes: A systematic review and meta‐analysis. Issue 5 (18th April 2013) - Corbella, Stefano; Francetti, Luca; Taschieri, Silvio; De, Francesca; Fabbro, Massimo Del
Abstract Aims/Introduction The aim of the present study was to investigate whether non‐surgical periodontal treatment reduces glycated hemoglobin (HbA1c) and fasting plasma glucose (FPG) levels in diabetic patients. Materials and Methods An electronic search was carried out on MEDLINE (through PubMed interface), EMBASE and the Cochrane Central Register of Controlled Trials. Randomized controlled trials with a minimum of 3 months follow up were included. The risk of bias was assessed for each study. A meta‐analysis was carried out to evaluate the effect of non‐surgical periodontal treatment on HbA1c and FPG levels. The effect of the adjunctive use of antimicrobials was also assessed. Results A total of 15 studies were included. A reduction of −0.38% (95% confidence interval [CI] −0.23 to −0.53) after 3–4 months (P < 0.001) and of −0.31% (95% CI 0.11 to −0.74) after 6 months (P = 0.15) of follow‐up was found for HbA1c, favoring the treatment group. Similarly, in treated patients, a significantly greater decrease in FPG was observed in respect to control participants. Such difference amounted to −9.01 mg/dL (95% CI −2.24 to −15.78) after 3–4 months (P = 0.009) and −13.62 mg/dL (95% CI 0.45 to −27.69) after 6 months (P = 0.06) from treatment, respectively. In participants treated with adjunctive antimicrobials, a non‐significant increase of HbA1c was observed 3 months after treatment, whereas FPG decreased by 0.27 mg/dL (95% CI 39.56 to −40.11; P = 0.99). Conclusions The meta‐analysis showed that non‐surgical periodontal treatment improves metabolic control in patients with both periodontitis and diabetes.